Efficient synthesis of 2,3-aziridino-gamma-lactones from azetidin-2-ones - Kale, Ajaykumar S.; Deshmukh, A. R. A. S. (Synlett, 2005)
An efficient synthesis of enantiopure 2,3-aziridino-gamma-lactones from azetidin-2-ones is described. Acid-catalyzed tandem intramolecular azetidinone ring opening followed by aziridine ring formation via elimination of a mesylate group is the key step in this synthesis. 2,3-Aziridino-gamma-lactones are important precursors for biologically important glutamic acid derivatives.
Keywords: azetidin-2-ones; aziridines; glutamic acid; lactones